Kemampuan Senyawa Anti Ketombe pada Sampo dalam Menghambat Pertumbuhan Jamur yang Diisolasi dari Ketombe - Mujahidah Basarang; Muh. Rifo Rianto; Riskiah Dwi Julianti (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Dandruff is a medical condition that indicates the activity or growth of fungi on the scalp. Shampooing using an anti-dandruff shampoo is an action that can be taken to inhibit the growth of these fungi. Anti-dandruff shampoo contains antifungal active compounds such as ZnPtO, selenium sulfide, piroctone olamine which functions in reducing fungal infections on the scalp which are expected to inhibit the growth of fungi found on the scalp that cause dandruff. This study aims to determine the inhibition of the active compound in anti-dandruff shampoo against fungal growth isolated from dandruff. This research is a laboratory experimental study which was carried out by isolating the fungus from dandruff and continued by testing the inhibition of fungal growth using a shampoo containing active compounds. From the results of research conducted on 3 shampoos that have different anti-dandruff compounds, namely ZnPtO, 1% selenium sulfide, and piroctone olamine, the growth of fungal colonies decreased with different contact times, namely 2 minutes, 4 minutes, and 6 minutes. The conclusion of the study stated that shampoo containing piroctone olamine compound with a contact time of 6 minutes inhibited the growth of fungal colonies better than other shampoos containing 1% selenium sulfide and zinc pyrithione (ZnPtO).